Clinical value of liver ultrasound for the diagnosis of nonalcoholic fatty liver disease in overweight and obese patients. (27th April 2015) - Bril, Fernando; Ortiz‐Lopez, Carolina; Lomonaco, Romina; Orsak, Beverly; Freckleton, Michael; Chintapalli, Kedar; Hardies, Jean; Lai, Song; Solano, Felipe; Tio, Fermin; Cusi, Kenneth
Abstract Background & Aims Liver ultrasound (US) is usually used in the clinical setting for the diagnosis and follow‐up of patients with nonalcoholic fatty liver disease (NAFLD). However, no large study has carefully assessed its performance using a semiquantitative ultrasonographic scoring system in overweight/obese patients, in comparison to magnetic resonance spectroscopy (1H‐MRS) and histology. Methods We recruited 146 patients and performed: a liver US using a 5‐parameter scoring system, a liver 1H‐MRS to quantify liver fat content, and a liver biopsy to assess histology. All measurements were repeated in a subgroup of patients (n = 62) after 18 months of follow‐up. Results The performance of liver US (parenchymal echo alone) was rather modest, and significantly worse than 1H‐MRS (AUROC: 0.82 [0.69–0.94] vs. 0.96 [0.90–1.00]; P = 0.04). However, the AUROC improved when different echographic parameters were taken into account (AUROC: 0.89 [0.83–0.96], P = 0.15 against 1H‐MRS). Optimum sensitivity for liver US was achieved at a liver fat content ≥12.5%, suggesting that below this threshold, liver US is less sensitive. Liver 1H‐MRS showed a high accuracy for the diagnosis of NAFLD, and correlated strongly with histological steatosis (r = 0.73, P < 0.0001). None of the imaging tests was adequate enough to predict changes over time in histology. Conclusions Despite its widespread use, liver US has several important limitations that healthcare providers should recognize, particularly because of its low sensitivity. Using a combination of echographic parameters, liver US showed a significant improvement in its diagnostic performance, but still was of limited value for monitoring treatment over time.